(untitled) (Global Journal of Science Frontier Research, 2021)
The influence of deposition conditions on the morphology and structure of the two-layer system TiN / Ni 0.905 W 0.095 were studied. The effect of concurrent formation of cube texture both in substrate based on paramagnetic alloy Ni 0.905 W 0.095 and TiN coating was detected by means of xray diffraction analysis. Composition TiN / Ni 0.905 W 0.095 may be used as a substrate in the conductive architecture of 2G HTS to improve its critical current density.